+0  
 
0
281
2
avatar

Solve for $x$: $$ \frac{3x+12}{x+4} = \frac{4x^2 + 8x + 8x^2}{2x}$$

Guest Oct 12, 2017

Best Answer 

 #2
avatar+771 
+2

\(\frac{3x+12}{x+4} = \frac{4x^2 + 8x + 8x^2}{2x}\)

First, you can take a 3 out of the numerator on the left.

\(\frac{3(x+4)}{x+4} = \frac{4x^2 + 8x + 8x^2}{2x}\)

Combine like factors on the top right.

\(\frac{3(x+4)}{x+4} = \frac{12x^2+8x}{2x}\)

The x+4's on the right can cancel.

\(3=\frac{12x^2+8x}{2x}\)

The left can be divided by 2x.

\(3=6x+4\)

Subtract 4 from both sides.

\(-1=6x\)

Divide both sides by 6.

\(x=-\frac{1}{6}\)

AdamTaurus  Oct 12, 2017
 #1
avatar+50 
+1

x=-1/6

Atroshus  Oct 12, 2017
 #2
avatar+771 
+2
Best Answer

\(\frac{3x+12}{x+4} = \frac{4x^2 + 8x + 8x^2}{2x}\)

First, you can take a 3 out of the numerator on the left.

\(\frac{3(x+4)}{x+4} = \frac{4x^2 + 8x + 8x^2}{2x}\)

Combine like factors on the top right.

\(\frac{3(x+4)}{x+4} = \frac{12x^2+8x}{2x}\)

The x+4's on the right can cancel.

\(3=\frac{12x^2+8x}{2x}\)

The left can be divided by 2x.

\(3=6x+4\)

Subtract 4 from both sides.

\(-1=6x\)

Divide both sides by 6.

\(x=-\frac{1}{6}\)

AdamTaurus  Oct 12, 2017

32 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.